Detection of Severe Acute Respiratory Syndrome‐Like, Middle East Respiratory Syndrome‐Like Bat Coronaviruses and Group H Rotavirus in Faeces of Korean Bats. Issue 4 (23rd May 2016) - Kim, H. K.; Yoon, S.‐W.; Kim, D.‐J.; Koo, B.‐S.; Noh, J. Y.; Kim, J. H.; Choi, Y. G.; Na, W.; Chang, K.‐T.; Song, D.; Jeong, D. G.
Summary: Bat species around the world have recently been recognized as major reservoirs of several zoonotic viruses, such as severe acute respiratory syndrome coronavirus (SARS‐CoV), Middle East respiratory syndrome coronavirus (MERS‐CoV), Nipah virus and Hendra virus. In this study, consensus primer‐based reverse transcriptase polymerase chain reactions (RT‐PCRs) and high‐throughput sequencing were performed to investigate viruses in bat faecal samples collected at 11 natural bat habitat sites from July to December 2015 in Korea. Diverse coronaviruses were first detected in Korean bat faeces, including alphacoronaviruses, SARS‐CoV‐like and MERS‐CoV‐like betacoronaviruses. In addition, we identified a novel bat rotavirus belonging to group H rotavirus which has only been described in human and pigs until now. Therefore, our results suggest the need for continuing surveillance and additional virological studies in domestic bat.